1978
DOI: 10.1042/cs054019pa
|View full text |Cite
|
Sign up to set email alerts
|

Local Production of IgG, IgA and IgE Antibody to Pollen Antigens in Patients with Hay Fever

Abstract: 19PFifteen untreated patients with a presumptive diagnosis of hypertension were studied for periods up to 48 h with the Oxford continuous intra-arterial pressure recorder. In each case a denned protocol of rest and exercise (using an Elema bicycle ergometer) was followed before the patients left the hospital. Blood pressure was characterized in each patient by a 6-hourly daytime mean systolic and diastolic measurement, and by peak responses to increasing levels of exercise. The 6-hourly mean pressures were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
3
5

Year Published

1982
1982
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(142 citation statements)
references
References 0 publications
8
126
3
5
Order By: Relevance
“…The mean proportion of JCP-specific IgE was approximately 100-fold higher than IgA and IgG (Table 1), in both the NLF and serum, and was quite consistent with previous studies with serum (19) or explant culture (20). Such a great difference among immunoglobulin classes could be rationalized by hypothesizing that certain restricted tissues, including the nasal mucosa, are dominantly responsible for total IgE production in modern environments.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The mean proportion of JCP-specific IgE was approximately 100-fold higher than IgA and IgG (Table 1), in both the NLF and serum, and was quite consistent with previous studies with serum (19) or explant culture (20). Such a great difference among immunoglobulin classes could be rationalized by hypothesizing that certain restricted tissues, including the nasal mucosa, are dominantly responsible for total IgE production in modern environments.…”
Section: Discussionsupporting
confidence: 65%
“…These results of specific IgE and IgG proportion were in good agreement with a study that mucosal explant from hay fever patients could produce IgE but not IgG antibody, in vitro (20). On the other hand, the data about IgG contrasts with a previous report that the specific proportion of IgG is higher in nasal discharge than in serum (19).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…32 In humans, IgG and IgA are produced locally as evidenced by the higher proportion of specific antibody to total immunoglobulin in nasal secretions. 33 Likewise, evidence for local IgE production can be found in tears. 34 Patients who are allergic to bee venom may remain sensitive decades after their last exposure.…”
Section: When and Where Does Class Switching Occur?mentioning
confidence: 99%
“…[215][216][217] Several studies have shown that levels of aeroallergen-specific IgE are much higher in the airways than in the serum when normalized to total IgE or albumin. [216][217][218][219][220][221][222] It is not uncommon for individuals with allergic rhinitis or chronic rhinosinusitis (CRS) to manifest antigen-specific IgE in nasal secretions or nasal tissue with no apparent specific IgE in the serum for the same antigen, and documented cases exist in which nasal antigen challenge responses are elicited in individuals that lack skin test sensitivity. 215,217,218,220 A survey study found that 19% of patients with rhinitis and polyposis had specific IgE in the nose but not the serum.…”
Section: B-lymphocytes In Chronic Diseases Of the Upper Airwaymentioning
confidence: 99%